PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII-1 SMP NEGERI 4 MUARA BATANG GADIS TP. 2021/2022 - Wilda Harianti; Yuni Rhamayanti; Puspa Riani Nasution (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2022)
This The low ability of students' mathematical problem solving affects the success of a learning process. Learning model as a tool to achieve a goal. The better a learning model, the better the achievement. So one of the most important teacher tasks, before carrying out their duties is to know and apply the learning model, the model used in this study is the Number Head Together (NHT) cooperative learning model.This research is a classroom action research (CAR) by taking the research subjects of Class VIII-1 students of SMP Negeri 4 Muara Batang Gadis for the academic year 2021-2022. consisting of 22 students. The objects taken in the research are students' problem solving abilities, student learning activities in the implementation of classroom learning, teacher activities that specialize in the Number Head Together (NHT) type cooperative learning model to improve students' mathematical problem solving on the subject of Two Variable Linear Equation Systems ( SPLDV). The results of this study show that the problem-solving ability of students using the Number Head Together (NHT) type of cooperative learning model for Class VIII-1 students of SMP Negeri 4 Muara Batang Gadis in the 2021-2022 academic year has increased, it can be seen from the students' mathematical problem solving ability in the first cycle of 45 ,45% who completed the second cycle and 81.82% of students who completed the 22 students who took the study test. Based on the research data through the student observers, the percentage was 68.75% in the first cycle and 90% in the second cycle. Based on the research data through teacher observers, the percentage was 3.45 in the first cycle and 3.94 in the second cycle. So, it can be concluded that each cycle has increased and is included in the